An Investigation of the Influence of Travel Bloggers and Vloggers on Consumer's Toursim Decision Making in China - Li, Xin-Ya (2018)
At present, the internet has become an important channel for consumers to obtain tourism information. Among the channels of tourism information sources, the official channels only account for a small part of the information. Most of the information comes from websites such as professional travel websites, tourism forums, and travel blogs via social media. It should be noticed that social media has occupied a significant position in the process of consumer’s tourism decision-making. Therefore, research on the impact of travel blogs on consumer’s decision making is necessary.